2022
DOI: 10.1038/s41598-022-07794-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of podoplanin in metastatic lymph node is associated with extranodal extension in oropharyngeal cancer

Abstract: This study aimed to investigate the spatial distribution and clinical significance of podoplanin expression in the metastatic lymph nodes of oropharyngeal squamous cell carcinomas (OPSCCs). The immunohistochemical podoplanin expression in the metastatic lymph nodes was evaluated in the pathologic specimens of 47 consecutive OPSCC patients. Clinicopathologic factors, including podoplanin expression and extranodal extension (ENE) status, were analyzed. Podoplanin was significantly expressed in the perinodal stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Indeed, the hypothesis that the molecular determinants of ECS are present in the primary tumor is supported by recent studies [58][59][60][61]. Meanwhile, several studies have investigated the role of tumor microenvironment in ECS tumor formation [50,57,[62][63][64] and suggested that phenotypic changes occur from intranodal metastasis to ECS, rather than the intrinsic properties of the primary tumor.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, the hypothesis that the molecular determinants of ECS are present in the primary tumor is supported by recent studies [58][59][60][61]. Meanwhile, several studies have investigated the role of tumor microenvironment in ECS tumor formation [50,57,[62][63][64] and suggested that phenotypic changes occur from intranodal metastasis to ECS, rather than the intrinsic properties of the primary tumor.…”
Section: Discussionmentioning
confidence: 96%